Targeting Myeloid-Derived Suppressor Cells to Enhance the Antitumor Efficacy of Immune Checkpoint Blockade Therapy - Li, Xueyan; Zhong, Jiahui; Deng, Xue; Guo, Xuan; Lu, Yantong; Lin, Juze; Huang, Xuhui; Wang, Changjun (Frontiers in Immunology, 2021)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that are activated under pathological conditions, such as cancer, or mature myeloid cells that are converted immune-suppressive cells via tumor-derived exosomes, and potently support the tumor processes at different levels. Currently, multiple studies have demonstrated that MDSCs induce immune checkpoint blockade (ICB) therapy resistance through their contribution to the immunosuppressive network in the tumor microenvironment. In addition, non-immunosuppressive mechanisms of MDSCs such as promotion of angiogenesis and induction of cancer stem cells also exert a powerful role in tumor progression. Thus, MDSCs are potential therapeutic targets to enhance the antitumor efficacy of ICB therapy in cases of multiple cancers. This review focuses on the tumor-promoting mechanism of MDSCs and provides an overview of current strategies that target MDSCs with the objective of enhancing the antitumor efficacy of ICB therapy.